Historical conditioning as the decisive factor in the contemporary spatial structure of Polish agriculture - MAZUR, Marcin (Discussion Papers, 2011)
Agricultural production in Poland and Polish exports of agricultural produce are developing dynamically. Yet, the share of farming in the national product and its significance on the labour market has been constantly decreasing since World War II. Nevertheless, in comparison with other countries of Central-Eastern Europe, and especially with those of Western Europe, Polish agriculture does still play an important role as a sector of the national economy. Numerous authors agree that the high significance of agriculture in Polish economy has an historical conditioning. The majority of contemporary analyses, concerning Polish agriculture, however, take up the subject of its dynamic transformations and the functioning in new circumstances, following the accession of Poland to the EU. It is, though, much less frequent to note that the spatial structure of Polish agriculture is still marked by distinct discontinuities and that this structure still reflects to a much higher degree the historical background than the financial support instrument application or even the natural conditions, the latter constituting the truly decisive factor in case of many countries. An exceptionally high importance of the historical factors, in comparison with other countries, can be explained by two facts: first, the division of Polish territory until 1914; and second, the shift of the national boundaries after the World War II and the socio-economic processes, associated later on with this fact. The degree of spatial differentiation of the qualitative and quantitative features of the Polish agriculture in different regions is, however, also bigger than that observed for the remaining sectors of economy. They underwent more dynamic transformations, both in the period of the socialist People’s Poland, and later on. One can, therefore, draw a conclusion on the relatively high inertia of agriculture in terms of the evening out of this differentiation across the territory of the country. The objective of the present paper is to demonstrate the persistent presence of the still decisive historical factors in the shaping of the spatial structure of modern agriculture. The analysis is based on the statistical and cartographic materials developed for the purposes of the Atlas of Polish Agriculture.